2009
DOI: 10.1007/s00595-009-4061-2
|View full text |Cite
|
Sign up to set email alerts
|

Tight perioperative glycemic control using an artificial endocrine pancreas

Abstract: Van den Berghe et al. reported in 2001 that tight glycemic control (maintaining blood glucose levels at 80-110 mg/dl) improved morbidity and mortality in the surgical intensive care unit. This method was termed intensive insulin therapy (IIT), and it is now being adopted worldwide for perioperative care. Recent evidence has suggested that perioperative hyperglycemia significantly contributes to the development of postoperative infection (POI). Many professional societies therefore now recommend IIT over conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…This equipment continuously monitors blood glucose concentrations by withdrawing blood from a peripheral vein and administers insulin or glucose at rates determined to maintain the target glucose concentration. Artificial endocrine pancreas was shown to be safe and efficient in achieving tight perioperative blood glucose control without hypoglycemic episodes even immediately after total pancreatectomy [54,55]. …”
Section: Treatmentmentioning
confidence: 99%
“…This equipment continuously monitors blood glucose concentrations by withdrawing blood from a peripheral vein and administers insulin or glucose at rates determined to maintain the target glucose concentration. Artificial endocrine pancreas was shown to be safe and efficient in achieving tight perioperative blood glucose control without hypoglycemic episodes even immediately after total pancreatectomy [54,55]. …”
Section: Treatmentmentioning
confidence: 99%
“…However, we evaluated the usefulness of the artificial pancreas during the 7-day acute phase after surgery in sepsis patients. Thus, the patients’ conditions and the period of use differed from the study by Hanazaki et al [16]. …”
Section: Discussionmentioning
confidence: 81%
“…Hanazaki et al [16 ]reported on the benefit of glucose control using STG-22. However, we evaluated the usefulness of the artificial pancreas during the 7-day acute phase after surgery in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid hypoglycemia in tight glycemic control and improve POI in surgery, the closed-loop artificial endocrine pancreas system is an effective and safe means. Furthermore, novel perioperative glycemic control using an artificial pancreas markedly improved the labor burden on nursing staff, and hence reduced concerns about hypoglycemia [43] . Finally, because an ideal comparative study of tight glycemic control should be carried out under conditions without risk of hypoglycemia, blood glucose control using a closed-loop artificial pancreas system might be beneficial for the detection of the optimal target range for blood glucose in surgical patients.…”
Section: Tight Perioperative Glycemic Control Using a Closed-loop Artmentioning
confidence: 99%